Perverse politics? : feminism, anti-imperialism, multiplicity - Orloff, Ann Shola; Ray, Raka; Savci, Evren (Political power and social theory, 2016)
The papers collected here offer anti-imperialist feminist alternatives to second wave feminism's often reductive understandings of freedom; emancipation; oppression; empowerment and democracy.